KEPRAKTISAN ENSIKLOPEDIA FAMILI ANNONACEAE DI KEBUN RAYA BANUA UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA - Nida, Nida; Zaini, Muhammad; Kaspul, Kaspul (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
Students' critical thinking skills are still very low. Development research is carried out to improve the quality of the product under development, namely the encyclopedia. An encyclopedia is learning material that includes descriptions and pictures to make topics clearer. Each statement is listed in alphabetical order for ease of use. This study aims to describe the viability of the Annonaceae family in the Botanical Garden of Banua. This study uses the developmental research type of instructional design research with Tessmer's formative assessment design. The personality test subjects were four students and the small group test subjects were four students who took the Phanerogamae course. Data were obtained from different research instruments on the practicality of content and the practicality of expectations. The results of the encyclopedic study of the family Annonaceae at the Botanical Garden of Banua on the practicality of the contents received a good category, because it received a very good category for its structure, attractiveness, and practicality because it is easy to use, and has received positive feedback from students.